Influencing of water droplets on corona inception characteristics of composite insulator recorded by UV imager. Issue 10 (19th February 2021) - Lü, Fangcheng; Niu, Leilei; Wang, Shenghui; Jiang, Tingyue; Li, Wei; Guo, Jiayi; Li, Hao
Abstract : Water droplets on the surface of insulators can distort the electric field and cause the generation of surface partial discharge or flashover. In this study, the inception and the development of surface partial discharges on a 110 kV composite insulator were evaluated by using a solar‐blind ultraviolet imager. Several experiments were conducted by using water droplets differing in volume, conductivity, and position on an insulator housing. The results showed that the corona inception voltage decreases with the increasing volume of the water droplets. The relative permittivity of the water droplet decreases with the increase of the conductivity and then reduces the electric field intensity and increases the corona inception voltage. Installing the grading ring can increase the value of the corona inception voltage by 38% at most. To investigate the influence of the water droplets on the corona inception characteristics of the insulator, the sheath and shed models were proposed according to the feature of the electric field distribution. By changing the parameters of the water droplets, the corona inception voltage, discharge position, and electric field were analysed. Furthermore, the flashover voltage of the water droplets is influenced by its conductivity, while the corona inception voltage by its relative permittivity.